1991
DOI: 10.1111/j.1151-2916.1991.tb06874.x
|View full text |Cite
|
Sign up to set email alerts
|

Substituted Tobermorites: 27Al and 29Si MASNMR, Cation Exchange, and Water Sorption Studies

Abstract: A1 and 29Si magic angle spinning nuclear magnetic resonance spectroscopy revealed that the maximum amount of Al that can be substituted for Si in the tobermorite structure is 15 to 20 mol%. Powder X-ray diffraction and cation exchange studies corroborate the above finding. Anomalous tobermorite structures resulted in all cases, and hydrogarnet appeared beyond the 15 to 20 mol% A1 substitution limit for Si. The sorption of water molecules by synthetic [A13+ + Na+]-substituted tobermorites and their cationexchan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 21 publications
1
35
0
Order By: Relevance
“…8a) indicates that the alumina tetrahedra occur in silicate chain [Q 2 (1Al)] and branching [Q 3 (1Al), Q 3 (2Al)] positions within the (002) interlayer (Komarneni and Roy 1983;Komarneni et al 1985;Tsuji et al 1991;Skibsted et al 1994;Sun et al 2006). The high intensity of Q 2 (0Al) and Q 2 (1Al) peaks relative to the Q 1 peak indicates long chain lengths in the b [020] crystallographic direction.…”
Section: C-a-s-h and Al-tobermorite Nexafs Spectra And Aluminum Coordmentioning
confidence: 97%
See 1 more Smart Citation
“…8a) indicates that the alumina tetrahedra occur in silicate chain [Q 2 (1Al)] and branching [Q 3 (1Al), Q 3 (2Al)] positions within the (002) interlayer (Komarneni and Roy 1983;Komarneni et al 1985;Tsuji et al 1991;Skibsted et al 1994;Sun et al 2006). The high intensity of Q 2 (0Al) and Q 2 (1Al) peaks relative to the Q 1 peak indicates long chain lengths in the b [020] crystallographic direction.…”
Section: C-a-s-h and Al-tobermorite Nexafs Spectra And Aluminum Coordmentioning
confidence: 97%
“…The poorly crystalline C-A-S-H binders of these concretes improve chemical stability relative to C-S-H, the "glue" of conventional Portland-type cement concretes, whose model basis is the ideal composition of tobermorite, Ca 5 Si 6 H 2 O 18 ·4H 2 O (Taylor 1992;Sun et al 2006). C-A-S-H and 11 Å Al-tobermorite hold great potential as cementitious binders for high-performance concretes and concrete encapsulations of hazardous wastes (Komarneni and Roy 1983;Komarneni et al 1987;Komarneni and Tsuji 1989;Tsuji et al 1991), but the long-term performance of C-A-S-H is unknown and neither pure tobermorite nor Al-tobermorite occur in moist air-cured conventional concretes. Although laboratory syntheses of Al-tobermorite typically require high temperatures, 120 to 240 °C (Diamond 1966;Komarneni and Roy 1983;Komarneni and Tsuji 1989; Barnes and Scheetz 1991;Shaw et al 2000;Sun et al 2006;Houston et al 2009), occasional syntheses have been achieved at 80 °C with amorphous silica and zeolites (Komarneni and Roy 1983;Komarneni et al 1985), reactants similar to zeolitized alkaliand alumina-rich Flegrean ash pozzolan (de'Gennaro et al 2000).…”
mentioning
confidence: 99%
“…The presence of this phase was confirmed with micro-Raman analysis. If Al 3+ is substituted for Si 4+ then tobermorite has a high absorption capacity for Cs, Sr, and other alkaline and alkaline-earth elements through ion exchange [8,21]. This phase has also been extensively studied because it incorporates Eu(III), which is oftentimes used as a surrogate for the trivalent actinides [22].…”
Section: Surface Analysesmentioning
confidence: 98%
“…metakaolinite, 8,11 kaolinite, 1 zeolite, 6 newsprint recycling residue 12 and y ash [14][15][16][17] ) and the optimization of its ion exchange performance. 4 It has also been reported that aluminum could inuence the formation of tobermorite to form Al-substituted tobermorite, in which Al substitution occurred at the Q 2 or Q 3 sites (the symbol Q represents one SiO 4 tetrahedron and the superscript indicates the number of other Q units to which it is bonded), 7 as illustrated in Fig.…”
Section: 13mentioning
confidence: 99%